Verbal and Visual Messages on “L’oreal Paris Men Expert” Advertisements - Bagus Surya Pratama, I Gusti Agung (Humanis; Vol 22 No 1 (2018), 2018)
The study entitled “Verbal and Visual Messages on ‘L’Oreal Paris Men Expert’ Advertisements” aims to identify and analyze the meaning and function of verbal and visual message taken from four L’Oreal Paris Men Expert advertisements. The data used for this study were collected using three parts of research, method and technique of collecting data, method and technique of analyzing data, and data source. The research explains about verbal and visual message and was conducted through the implementation of the signifier and signified theory proposed by Chandler (2001 ) , theory of functions proposed by Leech (1974) and theory of meaning specified in the meaning of colors in advertisement proposed by Cerrato (2012). The result of this study showed that the most used meaning in each advertisement has a conceptual meaning which is purposed to give literal concept without any other meanings beside it. The informational function is the most used function which gives clear information about the product in the advertisements. The relation among the four advertisements is quite simple. It is found that simplicity is the basic matter for men and it is proven by the analysis that men are simpler than women in many things.